The Relevance of Ibn Sina’s Thoughts in Facing Education in the Artificial Intelligence Era - Rifqi Khairul Anam; Abdelmajid Idris Mohammad Khalil (Journal of Contemporary Islamic Education, 2025)
This research investigates the impact of human dependence on AI in education and explores the relevance of Ibn Sina's philosophy as a framework for addressing this challenge. By analyzing scholarly literature on Ibn Sina's educational thought and AI in education, the study identifies key themes, such as the role of human reason, ethical considerations, and the potential impact of AI on learning. The findings suggest that Ibn Sina's emphasis on holistic development, including intellectual, ethical, and spiritual dimensions, offers valuable insights for contemporary education. The study concludes that by integrating Ibn Sina's principles with AI-driven education, educators can create learning environments that foster critical thinking, moral reasoning, and ethical decision-making, ensuring the holistic development of students in the digital age.